2023
DOI: 10.3390/mi14020312
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Microflyer Driven by a Microsized Charge Combined with an Initiation Criterion

Abstract: In order to study the performance of ultra-fine 2,2′, 4,4′, 6,6′–hexanitrostilbene (HNS-IV) explosives initiated by a microflyer driven by microsized lead azide (Pb(N3)2), a corresponding simulation model was established in Autodyn software, and the accuracy of the simulation model was verified with a photonic Doppler velocimeter (PDV). Various influencing factors were studied in combination with the power flux–action time (Π-τ) initiation criterion. The results showed that the exponential growth rate of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, the copper-based azide micro-initiator designed in this study exhibited excellent initiation performance. References [22,23] reported that 6 mg and 7.5 mg of copper azide were required for initiating CL-20 explosives, respectively, while reference [24] indicated that 4.6 mg of lead azide was needed for initiating HNS-IV explosives. In contrast, the copper-based azide synthesized in this study only required 0.8 mg to reliably initiate both CL-20 and HNS-IV explosives.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the copper-based azide micro-initiator designed in this study exhibited excellent initiation performance. References [22,23] reported that 6 mg and 7.5 mg of copper azide were required for initiating CL-20 explosives, respectively, while reference [24] indicated that 4.6 mg of lead azide was needed for initiating HNS-IV explosives. In contrast, the copper-based azide synthesized in this study only required 0.8 mg to reliably initiate both CL-20 and HNS-IV explosives.…”
Section: Discussionmentioning
confidence: 99%
“…The reliable completion of separation action by the spinning projectile's trajectory-end detection separation mechanism is crucial for the success of flight missions. The trajectory-end detection separation mechanism, as one of the core components of the projectile control system, utilizes target information, platform information, and environmental information to control the fuze according to a predetermined strategy [1][2][3]. When conducting dynamic research on separation mechanisms based on pyrotechnic separation, obtaining key geometric and physical parameters of the mechanism dynamics can be challenging.…”
Section: Introductionmentioning
confidence: 99%